Standards-Based Reform of Mathematics Education in Rural High Schools - Aimee Holwey; William Larson; Solange Andrianaivo; Megan Rhodes; Marged Howley (Journal of Research in Rural Education, 2007)
Researchers interviewed rural high school principals in order to learn about reform of mathematics education in their schools. Twenty principals from three rural regions of Ohio participated. A member of the research team conducted a semi-structured interview with each principal. Analysis of interview data suggested that schools were undertaking reform of mathematics education in response to state accountability standards and tests. Principals understood the reforms in a cursory way, recognizing that the reform agenda focused in a general sense on math for understanding, technology, and real world applications of mathematics. Their responses indicated that the reforms adopted at their schools neither fully embraced the reform agenda nor completely ignored it. Instead, the reforms tended to entail incremental changes involving curriculum alignment, minor modifi cations of curriculum content, and provision of individualized instruction.